Development of a Supported Ionic Liquid Phase (SILP) Catalyst for Slurry-Phase Friedel-Crafts Alkylations of Cumene - Joni, Joni; Haumann, Marco; Wasserscheid, Peter (dvanced Synthesis & Catalysis, 2009)
A supported ionic liquid phase (SILP) catalyst material has been developed based on a silica support coated with an acidic chloroaluminate ionic liquid. Compared to the results in a liquid-liquid biphasic reaction these materials showed in the isopropylation of cumene a clearly different selectivity which was found to be related to a reduction of the ionic liquid's acidity by the untreated silica support. By pretreating the support with a defined amount of ionic liquid for neutralization and removal of surface hydroxy groups, a well defined, very active and also very selective SILP catalyst for slurry phase Friedel–Crafts alkylation was obtained.